William Lowndes Yancey and the coming of the Civil War - Walther, Eric H., 1960- (Civil War America (Series), 2006)
Born in Georgia but raised in the North by a fiercely abolitionist stepfather and an emotionally unstable mother, Yancey grew up believing that abolitionists were cruel, meddling, and hypocritical. His personal journey led him through a series of mentors who transformed his political views, and upon moving to frontier Alabama in his twenties, Yancey's penchant for rhetorical and physical violence was soon channeled into a crusade to protect slaveholders' rights.